CAPBLAT Development and Testing: Computer-Assisted Assessment Tool for Problem Based Learning - Muhammad Qomaruddin; Azizah Abdul Rahman; Noorminshah A. Iahad (Proceeding of the Electrical Engineering Computer Science and Informatics, 2014)
Recent years, Computer-Assisted Assessment (CAA) has become increasingly important in education. This is indicated by many researches that focused on the development of computer-based assessment tool to help assess performances of students from various disciplines. This study contributes to education area with the research on the development of innovative computer-based tool for Problem-Based Learning (PBL) assessment. A web-based assessment tool, named CAPBLAT, has been developed. The tool incorporates some methods of PBL assessment process which framed within “Problem-Based Learning Assessment Framework”. The tool has been created for evaluating students’ achievements on the PBL approach. This paper presents the development and user acceptance test of the CAPBLAT. The study utilizes the tool within two PBL classes as a medium for testing in the duration of one semester. A total of forty students participated in the testing of the tool. During the study, questionnaires were administered to students. The results concerning the assessment tool acceptance demonstrate that students showed positive feedback and accepted the usage of CAPBLAT for the PBL assessment process. It is also proved that the use of CAA in PBL gives advantages for both of lecturers and students by providing them with detailed formative feedback on their learning achievements compared to conventional assessment. It also reduces lecturer’s tedious load by automating parts of the task of marking students’ work.